Specjalne potrzeby edukacyjne – samoocena wiedzy, umiejętności i postaw w przekonaniach przyszłych nauczycieli języków obcych przed i po szkole letniej - Stasiak, Patrycja; Kałdonek-Crnjaković, Agnieszka; Molska, Małgorzata (Neofilolog, 2024)
The study involved students of the Faculty of Modern Languages at the University of Warsaw (FML UW), who attended a course within a summer school (SL) on special educational needs in language education. The study aimed to observe the changes in participants’ knowledge and skills in the area of special educational needs (SEN), as well as their attitudes towards teaching students with dyslexia, attention-deficit/hyperactivity disorder, and on the autism spectrum. The second aim of the study was to check the participants’ satisfaction with the SL organization with the view of continuing this initiative at FML UW. Data were collected using a pre- and post-questionnaire with closed- and open-ended questions and post-SL interviews. Data were presented using descriptive and interferential statistics. Interviews were transcribed and coded thematically in the scope of the research questions. Findings showed that SL was a successful initiative. The participants gained knowledge and skills at a significant level (p < 0.05). The participants believed that teaching students with SEN was challenging but they remained uncertain whether working with students with SEN was stressful. The participants reported a significantly more satisfactory attitude after the SL. Pedagogical implications of the findings are discussed considering the agency and well-being of language teachers.